Bacterial adhesion to host tissues : mechanisms and consequences - Wilson, Michael, 1947- (Advances in molecular and cellular microbiology ;, 2002)
Bacterial adhesion to host cells/tissues is essential for maintaining normal, protective host microflora. It is also the crucial first stage in any infectious disease. The molecular mechanisms described in this book are therefore of great interest to microbiologists and those seeking means of preventing and treating bacterial infections.